Manajemen Strategi LAZISMU Jawa Barat dalam Mengelola Dana Zakat - Safitri, Diana; Sarbini, Ahmad; Yulianai, Yuliani (Tadbir: Jurnal Manajemen Dakwah, 2021)
This study aims to determine how strategic management in LAZISMU West Java, especially in managing zakat funds. This research is based on Riva’i’s thought in Yunus that strategic management consists of three processes, namely: (1) strategy formulation, (2) strategy implementation, (3) evaluation. The method used in this research is descriptive method. Data collection techniques by observation and interviews. Based on these findings, it can be concluded that strategic management in LAZISMU West Java consists of three processes: First, the formulation of a strategy which includes the formulation of a vision and mission, environmental analysis, determining goals and objectives and ending with determining the strategy. Second, the implementation of strategies that include organizing, functional synergy that regulates program implementation, and program procedures for zakat fund management starting from the collection, distribution and utilization of productive zakat. Third, evaluation of strategies from the process of strategy formulation and implementation.